Effect of Financial Literation and Financial Bias on Investment Decisions - Ekatama, Muhammad Faris; Sutrisno, (Advances in Social Sciences Research Journal, 2022)
At this time human awareness to have a decent life is very high, so financial planning is needed. One of the financial planning is an investment decision. In investing, many variables are thought to influence the decision. The purpose of this study is to examine several variables that influence a person's decision to invest. The variables studied were financial literacy and financial need which consisted of Overconfidence, Representativeness, Familiarity, and Risk Perception. The number of respondents in this study were 156 people who live in the Special Region of Yogyakarta, they consisted of students, university students, and working. The data were collected using a questionnaire with a Lichkert scale. Data analysis used multiple regression analysis with a significance level of 0.05. The results of the study found that financial literacy has a positive and significant effect, as well as Overconfidence, Representativeness, Familiarity and Risk Perception have a positive effect on investment decisions.